The revised COLIPA in vitro UVA method. (21st September 2012) - Moyal, D.; Alard, V.; Bertin, C.; Boyer, F.; Brown, M.W.; Kolbe, L.; Matts, P.; Pissavini, M.
Synopsis A multicentred study derived from the COLIPA in vitro UVA method was performed to assess the influence of test conditions on UVA protection factor (UVAPF) values in terms of amplitude, reproducibility between laboratories and correlation with in vivo UVA results. Eight products with a range of in vivo UVAPF from three to 29 were used. Two different types of plates, namely high‐roughness (5 μm) and low‐roughness (2 μm) plates, were used with a different application rate for each (1.3 mg cm−2 and 0.75 mg cm−2 respectively). The UVR dose applied to both plate types followed the same principle as the original test (1.2 J. cm−2 × UVAPF0). Strong, significant correlations between in vitro and in vivo UVAPF values were observed for both plate types (Pearson correlation > 0.9, P ≤ 0.01). The correlation and slope obtained with the low‐roughness plates confirmed the previous results obtained by COLIPA. Across all laboratories, higher UVAPF values were obtained on the high‐roughness plates (P < 0.01). Reproducibility of UVAPF values between laboratories was comparable between the two plate roughness values (low roughness, COV = 8%; high roughness, COV = 12%). Considering the in vitro/in vivo comparisons, a regression slope of 0.83 was observed for the low‐roughness plates, in comparison with a value of 1.05 for the high‐roughness plates. The accuracy of the method was improved, therefore, with the use of the high‐roughness plates. With a constraint to recommend the use of only one plate type in the COLIPA UVA in vitro Test, the high‐roughness plate was selected on an on‐going basis to limit variability of results and to provide better accuracy with in vivo data.